2018
DOI: 10.1021/acs.jproteome.8b00456
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Serum Metabolomics of Patients with Takayasu Arteritis: Relationship with Disease Activity

Abstract: Takayasu arteritis (TA) is a large vessel vasculitis of unknown pathogenesis. Assessment of disease activity is a challenge, and there is an unmet need for relevant biomarker(s). In our previous study, NMR based serum metabolomics had revealed distinctive metabolic signatures in TA patients compared with age/sex matched healthy controls and systemic lupus erythematosus (SLE). In this study we investigate whether the metabolites correlate with disease activity. Patients with TA fulfilling American College of Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…A larger study, conducted by Jain et al in another cohort, confirmed these results and confirmed the role of glutamate and NAG as potentially strong biomarkers of TA [129].…”
Section: Rare Vascular Diseasessupporting
confidence: 61%
See 1 more Smart Citation
“…A larger study, conducted by Jain et al in another cohort, confirmed these results and confirmed the role of glutamate and NAG as potentially strong biomarkers of TA [129].…”
Section: Rare Vascular Diseasessupporting
confidence: 61%
“…Takayasu arteritis N-Acetyl glycoproteins are significantly up-regulated in TA patients [129,130] Kawasaki disease High levels of GlycA were confirmed in paediatric population with acute KD disease [110]…”
Section: Rare Vascular Diseasesmentioning
confidence: 97%
“…Nuclear Magnetic Resonance Spectroscopy (NMR) based serum metabolomics has identified distinct profiles in individuals suffering from TA in comparison to age- and sex-matched controls (56). The best discriminatory potential was found for N-acetyl glycoprotein (NAG), an anti-inflammatory metabolite, and glutamate, a neurotransmitter often associated with inflammation (5658). Upon follow up, changes in metabolic spectra evolved with a change in disease activity.…”
Section: Large Vessel Vasculitismentioning
confidence: 99%
“…Upon follow up, changes in metabolic spectra evolved with a change in disease activity. Thus, certain metabolic profiles allow the distinction between clinically active and inactive TA patients, representing potential biomarkers for disease activity and delivering additional information which can serve as a guide to therapy (56). Future studies should further investigate these findings in larger cohorts with a longer follow up duration.…”
Section: Large Vessel Vasculitismentioning
confidence: 99%
“…A limited number of studies have successfully applied metabolomics as a potential candidate biomarker for disease activity in vasculitis. Its use in Takyasu's arteritis (TA) has been evaluated, demonstrating good ability to distinguish active from quiescent disease, with acute phase protein associated N‐acetyl glycoprotein (NAG) as the key discriminating metabolite [22,23]. Al‐Ani et al analysed the urinary metabolomic profile in cases of renal limited AAV, demonstrating good discriminatory capacity with hypocitraturia and raised levels of myo‐inositol associating with active disease [24].…”
Section: Discussionmentioning
confidence: 99%